BANK DALAM MENGHADAPI ERA DISRUPSI FINTECH STRATEGI PERTUMBUHAN BISNIS BRILINK DEMI MENINGKATKAN PENDAPATAN MENGGUNAKAN KERANGKA KERJA MODEL BISNIS KANVAS (Studi Pada PT. Bank Rakyat Indonesia, Persero Tbk.) - Widya Hadi Nugraha; Susilo Toto Raharjo (ITB AAS INDONESIA, 2023)
BRILink is a service for BRI Bank to reach a wider market through collaboration with the community to become a BRILink agent that can serve banking transactions with a sharing fee system. However, the problem that occurs is that business competition in similar services is increasingly competitive. Therefore, the purpose of this study is to find out the application of the Canvas Business Model as a BRILink business growth strategy to maintain and increase competitive advantage in Indonesia so that the profitability of Bank BRI is well maintained. This research is a qualitative research with sample selection by purposive sampling. Samples who became informants were senior managers and managers of the BRILink Network Division. Methods of data collection using direct interviews. The results of the interviews were then observed to determine the company's internal environment in the form of strengths and weaknesses, and the external environment in the form of opportunities and threats as well as to determine the Business Canvas Model of BRILink. Data analysis starts from collecting data directly through interviews, reducing data, presenting data, to drawing conclusions. The results of the study prove that through the integration of SWOT analysis and the Business Canvas Model on the BRILink business, the company finds that the company has new strategic innovation opportunities, namely by supervising, empowering, and providing training to new agents to achieve competitive advantage so that they are able to grow and develop to reach a bigger market. large.